Um modelo experimental de estimulação transcraniana por corrente contínua em camundongos - Eduardo de Souza Nicolau (2018)
Transcranial direct current stimulation (tDCS) is a non-pharmacological and non-invasive therapeutic technique which principals consist in delivering low intensity currents to the human scalp evoking neuronal excitation (anodal stimulation) or inhibition (cathodal stimulation). Furthermore, it has been proposed as an alternative or complementary treatment for psychiatric diseases. It has also been used as a human enhancement therapy, improving motor and cognitive tasks. Despite an increase in clinical studies, there is still much to be learned from its overall mechanisms. Unfortunately, there are limitations that hinders further investigation of tDCS effects in the human brain. Therefore, the use of animal-tDCS models are of utmost importance and may bring great insight. In this work we proposed an easy and fast to execute tDCS model, supported by efficiency markers (genetic expression alterations) and data related to further investigating tDCS mechanisms (molecular and behavioral profiles). Data showed a viable stimulation model, executable in up to 30 minutes and resistant to longer periods of stimulation (5-day contact quality, p=n.s., 10-day contact quality p=n.s.). Concurrently, anodal tDCS over cortex M1 and M2 of 5 days (1-session/day, 10 min. 350 µA) increased the expression of BDNF (p=0.0081), a strongly cognitive associated gene and GFAP (p=0.0108) an astrocyte marker, expression levels in stimulated (tDCS) vs. non-stimulated (Sham) mice. This data was found to be specific for this protocol, whereas increase stimulation sessions and session disruption did not evoke any molecular alterations. In addition, gene expression alterations were restricted to these genes, once none of the other 8 neuronal associated genes tested suffered modulation. This model also presented enhanced learning performance in the Barnes Maze task, with a decrease in errors (p=0.0463), time taken (p=0.0409) and distance traveled (p=0.0105) to execute the task. Interestingly, the increased performance was attributed to an adaptation in more efficient (direct and serial – p=0.0003) strategies by the stimulated animals. Glutamate concentrations were also assessed but did not present significant differences. Overall, the presented model should attend as a future reference in animal model development and serve to investigate and describe additional tDCS underlying mechanisms, bringing light to tDCS real potential.